Seasonal Variations of Some Physio-Chemical Parameters of Al-Auda Marsh in Maysan Province - H. Al-Thahaibawi, Basim .M.; K.Al-Hiyaly, Sedik.A.; A. Al-Mayaly, Ithar .K. (Iraqi Journal of Science, 2023)
Seasonally variations in Physio-chemical parameters of Al-Auda Marsh were investigated from November 2012 to July 2013. In this research examine pH, turbidity, EC, DO, BOD5 and Ca+2, Mg+2, NO2 , NO3 , PO4 , SiO3 ions. Six sites were randomly located and water samples. pH values varied from (7.3 ±0.0) in site 4 during autumn to (8.5±0.5) in site 6 during winter, EC values ranged from (2020±186) μ.s/cm in site 5 during autumn to (6390±875) μ.s/cm in site 6 during summer, mean turbidity data were found to vary from (6.5 ±1.8) NTU in site 4 in summer to (31.0 ±1.6) NTU in site 3 in autumn. DO highest mean value (10.9 ± 0.6) was for site 6 in autumn and the lowest value (6.5±0.9) mg/l for site3 in spring. In case of BOD5 highest and lowest mean values were (4.8 ±0.3) mg/l in site 3 during autumn and (1.2 ±0.3) mg/l in site 2 during winter. Mean Ca+2 ions ranging from (46±9.4) mg/l in site 4 during autumn to (361±19.6) mg/l in site 1 during summer, mean value of Mg+2 ion varied from (18 ±9.5) mg/l in site 5 in autumn to (274 ±44.2) mg/l in summer for site 1. Also, mean PO4-3 values of varying from (0.01±0.0) mg/l in sample of site 6 during winter to (0.3±0.08) mg/l in sample of site 6 during spring. The mean NO3 values was varied from (1.8±0.8) mg/l in site 6 during winter to (6.9 ±0.5) mg/l in site 5 during autumn while in case of NO2 were (0.1±0.0) mg/l in both sites 5 and 6 during spring to (0.35 ±0.01) mg/l in site 1 during autumn. SiO3 data found to vary from (1.0±0.5) mg/l in site 6 during autumn to (6.35 ±0.5) mg/l in site 2 during summer.